Działalność Zgromadzenia Salezjańskiego na płaszczyźnie wychowania ku wartościom moralnym i społecznym - Gocko SDB, ks. Jerzy (Annales. Etyka w Życiu Gospodarczym, 2010)
This article portrays the most important elements of the Salesian formation and education in the context of social life. It also points out the specifics of the community and its charism which set the foundations for this congregation. The conclusion is a reflection on the key elements of the Salesian mission in the present world.